Google Classroom Adoption as Learning Management System in Senior High School Using Technology Acceptance Model - Panergayo, Albert Andry Echor; Aliazas, John Vincent Callo (FKIP Universitas Lampung, 2023)
Google Classroom Adoption as Learning Management System in Senior High School Using Technology Acceptance Model. Objectives: The purpose of this study was to determine the acceptance of Google Classroom as a learning management system for public high school at one state university in Laguna, Philippines, using the Technology Acceptance Model (TAM). It further determined the effect of online learning self-efficacy on the original TAM-related factors. Methods: Using a quantitative through survey method, the data were collected using a web-based program from 742 students and were analyzed using structural equation modelling. The content-validated research instrument was adapted from previous studies (Al-Maroof & Al-Meran, 2018; Fathema et al., 2015; Zimmerman and Kulikowich, 2016). Findings: Findings revealed that all hypotheses were supported. Both perceived ease of use (PEOU) and perceived usefulness (PU) positively influence the attitude towards use (ATU), according to the study's findings. The PU and ATU can likewise significantly predict behavioral intention to use (BIU), which in turn explains the actual usage (AU) of Google classrooms. Furthermore, Online learning self-efficacy (OLSE) demonstrates a positive impact on both PU and PEOU. Conclusion: This study concludes that the students found Google Classroom as an effective tool for teaching and learning, as evidenced by a positive perspective and strong intent to continue using the platform. The salient implications for implementing LMS-based courses and future lines of research were also discussed. Keywords: behavioral intention to use, online learning self-efficacy, perceived ease of use, perceived usefulness, technology acceptance model.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202355